University Administrators’ Leadership Style Influencing Instructors’ Job Satisfaction in Shanxi, China - Zhang Yayu (Pacific International Journal, 2024)
This paper investigates the relationship between university administrators' leadership styles and instructors' job satisfaction at Communication University of Shanxi, China. Job satisfaction is crucial for enhancing education quality and productivity, as it positively impacts instructors' motivation and dedication to teaching and research. University administrators play a pivotal role in shaping the work environment and culture. Different leadership styles, including transformational, transactional, and servant leadership, can significantly influence faculty engagement and motivation. The study focuses on the unique cultural and regional context of Shanxi, China, where local norms and policies influence leadership practices. The qualitative study's findings reveal prevalent leadership styles: transformational leaders inspire excellence, transactional leaders clarify expectations, and servant leaders support professional growth. Instructors' job satisfaction is influenced by professional development opportunities, collegial relationships, and fair compensation and recognition. The research highlights the strong link between leadership styles and job satisfaction, offering valuable insights for leadership development and policies to improve instructors' well-being. These findings hold practical implications for Communication University of Shanxi and the broader landscape of higher education in China.